2021
DOI: 10.1016/j.breast.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of platinum-based chemotherapy in patients with advanced breast cancer: An 11-year single institutional experience

Abstract: Background/methods: Although the prognosis of metastatic breast cancer (BC) has improved, some patients still develop high burden metastases or visceral crisis (VC) and polychemotherapy is commonly used in these cases. Data reporting the real effectiveness of this strategy are scanty. Therefore, the outcomes of patients with metastatic BC treated with platinum-based chemotherapy (P-ChT) at the Jules Bordet Institute during the period of January 2008 and December 2018 were retrospectively reviewed. The presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 49 publications
4
34
0
Order By: Relevance
“…This is similar to our findings (49.5 years). We found that the majority (118 cases, 89.39%) of patients with VC were older than 60 years, invasive ductal carcinoma was the most common pathological type (123 cases, 93.18%), and HR+, Her-2 − type was the most common molecular type (92cases, 69.18%), which was consistent with the reported literature (2,11).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is similar to our findings (49.5 years). We found that the majority (118 cases, 89.39%) of patients with VC were older than 60 years, invasive ductal carcinoma was the most common pathological type (123 cases, 93.18%), and HR+, Her-2 − type was the most common molecular type (92cases, 69.18%), which was consistent with the reported literature (2,11).…”
Section: Discussionsupporting
confidence: 91%
“…We found that between 2018 and 2022, VC occurred in 18.14% of 733 patients with advanced disease who were treated at the First Hospital of Jilin University and diagnosed with breast cancer VC. DLM was the most common VC type (50.38%), which is consistent with the findings of Maria et al (Supplementary Table S5) (2).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations